Efektivitas Program Permakanan Bagi Penyandang Disabilitas Miskin Kelurahan Darmo Kecamatan Wonokromo Kota Surabaya - Radhiyah Rahma Kartika; Susi Hardjati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Program of food for poor people with disabilities Kelurahan Darmo is one of the efforts to realize welfare carried out by the Surabaya City Government through the provision of healthy and nutritious food as a form of protection and social security. The purpose of the study was to analyze the effectiveness of food programs for poor people with disabilities in Kelurahan Darmo, Surabaya City. The research was conducted using a descriptive qualitative approach. Collecting research data using observation techniques, interviews, and documentation. To be able to determine the effectiveness or success of the food program using the theory of effectiveness, namely: understanding the program, being on target, on time, achieving goals, and real changes. The results of the research show: 1) The implementers have a good understanding of the program that is run through the socialization of the program 2) The target of the food program for poor people with disabilities in Darmo Village has complied with the established criteria 3) The use of time in providing food is not efficient 4) Purpose that has been determined has been achieved well 5) There are several positive impacts that are felt by the beneficiaries after becoming part of the program targets. It can be concluded that the implementation program of food for poor people with disabilities Kelurahan Darmo has not been fully implemented properly, it is necessary to improve several things related to the implementation of the program